Determining the factors influencing efficiency of property industry with Tobit model - Abdullah, Muhammad Ridhuan Bos; Maamor, Selamah; Abdul Karim, Mohd Zaini (2018)
This study is to analyse the factors that influence efficiency of Malaysian real estate industry by focusing on real estate firms in Malaysia.As for the first step, we analyze the efficiency in the real estate industry by estimating three different types of efficiency utilizing a modern frontier efficiency methodology named data envelopment analysis (DEA).Meanwhile Tobit Model employed in the second step to analyse the factors that influence efficiency found in first step.The data employed in this research is from 67 real estate firms listed in the Kuala Lumpur Stock Exchange (BSKL) in 2012.The results indicate that the highest average efficiency score is 0.70 which is being achieved by 23 firms or 34% of the listed firms operate at the efficient level. Regression result shows that profit, market share, and foreign share influence the efficiency of the real estate firm positively, meanwhile the cost affect the efficiency negatively as predicted.